Analytical modelling of permanent magnet synchronous machines - Connelly, Ross (2014)
This report contains a comprehensive evaluation of the Final Year Project (FYP), Analytical Modelling of Permanent Magnet Synchronous Machine (PMSM). It will give a full assessment of the motivation behind the project, the project objective, the background theory of the PMSM, the literature review, objectives/milestones, results, analysis, overall conclusions and suggestions of any future work or improvements that could be made on the project.